Methodological analysis of synthesizing graphene from carbon source solvents - Sedigheh Mousanezhad; Hooman Bakhshi (Scientific Reports)
Abstract This study conducts a methodological analysis of synthesizing graphene from carbon source solvents such as ethanol via self-condensation. The previous methods for fabricating graphene structures from carbon-containing solutions involve intricate multi-step processes that are predicated on specific laboratory configurations, including the utilization of reactors and protective atmospheres, which, due to their complexity, restrict scalability and impede industrial implementation. We have devised a more streamlined methodology by reevaluating the process, which eliminates the necessity for complex laboratory equipment and harsh conditions, thereby facilitating a more practical and scalable route to industrial graphene production. It adheres to green chemistry principles, allowing for the scalable synthesis of graphene oxide (GO) and rGO nanostructures at relatively low temperatures.